Ecological diversification of the Australian Coptotermes termites and the evolution of mound building. (20th March 2017) - Lee, Timothy R. C.; Evans, Theodore A.; Cameron, Stephen L.; Hochuli, Dieter F.; Ho, Simon Y. W.; Lo, Nathan
Abstract: Aim: The Australian Coptotermes (Family: Rhinotermitidae) are a small monophyletic group of termites, some of which build mounds. In this study, we construct predicted distributions based on environmental data (niche models) for all Australian species of Coptotermes to test whether specific environmental factors have contributed to the evolution of mound‐building behaviour and whether the degree of niche similarity and degree of phylogenetic similarity are correlated. Location: The Australian mainland, including the known native ranges of all Australian species of Coptotermes . Methods: We estimated the phylogenetic relationships between the species of Australian Coptotermes . We then generated and compared environmental niche models in a phylogenetic framework for all study species to test niche conservation. Our analyses were based on location data from our own sampling and from the Atlas of Living Australia, genetic data from a previous study of Australian Coptotermes, and environmental data from WorldClim and ASRIS. Results: We found that no environmental variable differed consistently between mound‐building and non‐mound‐building taxa and that the differences in niches between pairs of Australian species of Coptotermes are uncorrelated with time since divergence. The environmental tolerances of the Australian Coptotermes termites are more restricted by rainfall than they are by soil or temperature. Main conclusions: Our results show that mound‐building behaviour has not necessarily evolved in response to similar abiotic conditions. Our results are consistent with ecological speciation leading to niche divergence since Coptotermes first arrived in Australia ~12.5 million years ago.